2022
DOI: 10.3390/ijerph19052538
|View full text |Cite
|
Sign up to set email alerts
|

Patient Perceptions on Receiving Vaccination Services through Community Pharmacies

Abstract: (1) Introduction: Pharmacists are medical professionals who play an active role in the protection of public health. Since 2021, pharmacists with an appropriate certification have been authorised to administer vaccines against COVID-19. (2) Objective: The objective of this study was to ascertain the perceptions of patients about receiving vaccinations through community pharmacies. (3) Material and methods: This study was conducted in 2021. The research tool was an anonymous questionnaire published on the websit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“… 16 Participants preferred vaccination in pharmacies due to their proximity to homes and the abundance of pharmacies, making vaccination more accessible. 26 Recent studies also highlight that pharmacy vaccination services complement those offered by family physicians, especially appealing to working-age individuals due to convenience and accessibility. Additionally, the active involvement of pharmacists in routine care, including regular vaccine status checks, proactive conversations, vaccination recommendations, and immunization programs in pharmacies, presents further advantages.…”
Section: Discussionmentioning
confidence: 99%
“… 16 Participants preferred vaccination in pharmacies due to their proximity to homes and the abundance of pharmacies, making vaccination more accessible. 26 Recent studies also highlight that pharmacy vaccination services complement those offered by family physicians, especially appealing to working-age individuals due to convenience and accessibility. Additionally, the active involvement of pharmacists in routine care, including regular vaccine status checks, proactive conversations, vaccination recommendations, and immunization programs in pharmacies, presents further advantages.…”
Section: Discussionmentioning
confidence: 99%
“…The new coalition collected evidence and showed that vaccinations at pharmacies are safe and desired by society [21,31]. This was confirmed by a pharmacist's readiness and patient satisfaction checks [32,33]. The COVID-19 pandemic accelerated the development of competencies to qualify for vaccinations in the case of other HCPs in Poland.…”
Section: Engagement Of the Ministry Of Labor And Employer's Organizat...mentioning
confidence: 99%
“…Previous research conducted worldwide showed that there were several factors affecting provision of the service in community settings, such as, pharmacists knowledge and skills, community pharmacy resources, patient acceptability. 16 , 17 , 18 A study conducted in Saudi Arabia indicated that pharmacists showed positive attitudes towards providing clinical services to patients. 19 However, to the best of the authors' knowledge, this is the first qualitative study investigating community pharmacists' perceptions about providing Covid-19 vaccines in Saudi community settings.…”
Section: Introductionmentioning
confidence: 99%